Comparative mechanisms of PAH toxicity by benzo[a]pyrene and dibenzo[def,p]chrysene in primary human bronchial epithelial cells cultured at air-liquid interface - Chang, Yvonne (Toxicol Appl Pharmacol, 2019)
Current assumption for assessing carcinogenic risk of polycyclic aromatic hydrocarbons (PAHs) is that they function through a common mechanism of action; however, recent studies demonstrate that PAHs can act through unique mechanisms potentially contributing to cancer outcomes in a non-additive manner. Using a primary human 3D bronchial epithelial culture (HBEC) model, we assessed potential differences in mechanism of toxicity for two PAHs, benzo[a]pyrene (BAP) and dibenzo[def,p]chrysene (DBC), compared to a complex PAH mixture based on short-term biosignatures identified from transcriptional profiling. Differentiated bronchial epithelial cells were treated with BAP (100-500 μg/mL), DBC (10 μg/mL), and coal tar extract (CTE 500-1500 μg/mL, SRM1597a) for 48 hrs and gene expression was measured by RNA sequencing or quantitative PCR. Comparison of BAP and DBC gene signatures showed that the majority of genes (~60%) were uniquely regulated by treatment, including signaling pathways for inflammation and DNA damage by DBC and processes for cell cycle, hypoxia and oxidative stress by BAP. Specifically, BAP upregulated targets of AhR, NRF2, and KLF4, while DBC downregulated these same targets, suggesting a chemical-specific pattern in transcriptional regulation involved in antioxidant response, potentially contributing to differences in PAH potency. Other processes were regulated in common by all PAH treatments, BAP, DBC and CTE, including downregulation of genes involved in cell adhesion and reduced functional measurements of barrier integrity. This work supports prior in vivo studies and demonstrates the utility of profiling short-term biosignatures in an organotypic 3D model to identify mechanisms linked to carcinogenic risk of PAHs in humans.